Micro-Mousterian in northern Dalmatia - Vujević, Dario; Perhoč, Zlatko; Ivančić, Tomislav (Quaternary international, 2017)
The Zadar region is exceptionally rich in Middle Palaeolithic materials discovered in the area from Ražanac and Nin to the Zadar islands (Dugi otok, Silba and Pag). Sites correspond closely to raw material choice, as well as typological and technological characteristics of tools. Distinct microlithization is the main factor by which industries such as the Micro-Mousterian are classified. These kinds of materials are also characterized by preserved cortex on the core and tools made on primary and secondary flakes. The abundance and accessibility of smaller sized raw materials led Neanderthal groups to develop techniques that maximized tool size in as efficient manner as possible.